Registration Officers' Perception Towards The Implementation Of The Electronic Medical Record System At RSAD TK.II Udayana, Denpasar City - Cok Istri Nadya Anastashya Valensy; I Made Sudarma Adiputra; Anak Agung Gde Oka Widana (International Journal of Health Engineering and Technology, 2026)
The implementation of electronic medical records in all health care facilities is required to implement an electronic-based medical record system, as regulated in the Minister of Health Regulation Number 24 of 2022 concerning Medical Records. The purpose of this study was to determine the perceptions of registration officers regarding the implementation of the electronic medical record system at RSAD Level II Udayana, Denpasar City. This study used a qualitative approach with an in-depth interview method based on the Technology Acceptance Model (TAM) theory, which includes perceptions of ease of use, perceptions of benefits, attitudes toward use, and intentions to use the electronic medical record system. The results showed that the electronic medical record system was considered relatively easy to use after going through the adaptation and training process, and provided benefits in the form of increased work efficiency. Officers' attitudes toward using the system tended to be positive because they felt comfortable and helped in their work, and their intention to continue using the system was also high, driven by policies and developments in digital technology, despite technical obstacles such as internet network disruptions. From this study, it can be concluded that the acceptance of the electronic medical record system is influenced by a combination of ease of use, perceived benefits, and organizational and infrastructure support. Therefore, system quality improvement and ongoing training are needed to optimize implementation.